Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Metode Simple Additive Weighting (SAW) (Studi Kasus di PT MNC Sky Vision Tbk) - Simbolon, Marice Hotnauli; Sartana; Maranata Pasaribu (Jurnal Mahajana Informasi, 2023)
MNC Sky Vision (formerly known as PT Matahari Lintas Cakrawala) is a company involved in operating the first Pay TV in Indonesia. The problem of evaluating employee performance is something that cannot be avoided in today's world of work. Assessment by voting with the most votes is still considered ineffective because the measurement of values ​​is still guided by interpersonal relationships and the principle of conscience. To be able to improve the quality of good employee performance and to be able to support the company's progress, especially at PT MNC Sky Vision Tbk, the agency needs a stage of improvement and system development in a good and directed management process, based on this the researcher wants to provide a solution to solving the problem through the title research “Decision Support System for Selection of the Best Employees Simple Additive Weighting (SAW) Method (Case Study at PT MNC Sky Vision Tbk).